Temrezli’de (Sorgun, Yozgat) Yetiştirilen Triticum Sativum Bitkisinde U ve Th Birikimi ve Taşınması - Kırat, Güllü; Aydın, Nasuh (Fırat University, 2019)
Bu çalışmada, Temrezli tarım alanlarında yetiştirilen Triticum sativum L. (T. sativum) bitkisinden 20 adet örnek alınarak, bu bitkinin dal, kabuk ve tohumlarındaki uranyum ve toryumun (U ve Th) dağılımı ve akümülasyonu (birikimi) tanımlanmıştır. Bitki külü ve ilişkili toprak örneklerinde U ve Th’u belirlemek için ICP-MS ile analiz edilmiştir. T. sativum bitkisinin topraklarında, saplarında, kabuklarında ve tohumlarında ortalama U ve Th değerleri (sırasıyla), 2.73 mg/kg, 0.16 mg/kg, 0.17 mg/kg, 0.16 mg/kg ve 34.01 mg/kg, 1.02 mg/kg, 0,65 mg/kg, 1,09 mg/kg olarak bulunmuştur. Bu bitkinin ortalama U ve Th zenginleştirme katsayıları 1'den düşüktür. EC değerlerinin düşük olması, bitki organlarının metalin doygunluğundan kaynaklanabilir. Bu nedenle, T. sativum bitkisi, U ve Th tarafından kirlenen alanların iyileştirilmesinde ve fitoremeditasyonunda kullanılabilir.

In this study, 20 samples Triticum sativum L. (T. sativum) plants grown in Temrezli agriculture areas were collected and the distribution and accumulation of uranium and thorium (U and Th) in stems, shells and grains of this plant were identified. In addition, plant ashes and nearby soil samples were analyzed by ICP-MS to determine the concentrations of U and Th. The mean U and Th values in the soils, stems, shells and grains of T. sativum plant, were calculated as 2.73 mg/kg, 0.16 mg/kg, 0.17 mg/kg, 0.16 mg/kg and 34.01 mg/kg, 1.02 mg/kg, 0.65 mg/kg, 1.09 mg/kg (in respectively). The mean U and Th enrichment coefficients of this plant were less than 1. The decrease in EC may be due to the saturation of metal uptake and/or transport. Therefore, T. sativum plant may be useful in phytoremediation and in remediation areas contaminated by U and Th.
U and Th Transport and Uptake in Triticum Sativum Cultivated Farmland in the Temrezli (Sorgun, Yozgat, Turkey) U and Th Mining Area
Keywords: Engineering; Mühendislik